La « femme·eux·ze » musique québécoise - Blais-Tremblay, Vanessa (2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.
Keywords: 2000 à aujourd'hui; DIG; amériques; approches et analyses; bibliographie; discipline; discours dominant; genre; identités LGBTQIA2+; musique; outils; ouvrages de références; périodes historiques; québec; régions géographiques; sexualité; systèmes d'oppressions; thématiques

All these poses, such beautiful poses: Articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright's direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an "utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo." Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright's musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the "Clone." In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.
https://esploro.libs.uga.edu/esploro/outputs/9949334528002959
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; approches et analyses; arts; culture populaire; discipline; discours dominant; ethnographie; genre; hétérosexisme; masculinité; musique; mémoires/thèses; périodes historiques; queer; ressource en ligne; systèmes d'oppressions